2003
DOI: 10.1002/job.214
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of success in the era of the boundaryless career

Abstract: SummaryThe present study examines three classes of career competencies proposed as important predictors of success in the boundaryless career. Three criteria of career success were examined: perceived career satisfaction, perceived internal marketability, and perceived external marketability. Using data from 458 alumni from a large southeastern university, predictions were tested using partial correlations and dominance analysis. The results found support for the importance of 'knowing why,' 'knowing whom,' an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
693
1
38

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 694 publications
(754 citation statements)
references
References 49 publications
22
693
1
38
Order By: Relevance
“…failed to find a significant relationship between openness and career success (number of promotions and career satisfaction). Eby et al (2003) found significant effects only between openness and perceived career success. One explanation is that the subjects of this study differed from those in previous research.…”
Section: Discussionmentioning
confidence: 89%
“…failed to find a significant relationship between openness and career success (number of promotions and career satisfaction). Eby et al (2003) found significant effects only between openness and perceived career success. One explanation is that the subjects of this study differed from those in previous research.…”
Section: Discussionmentioning
confidence: 89%
“…For example, personality characteristics are included in some conceptualizations of employability, career capital, and career motivation (Eby, et al, 2003;Fugate, et al, 2004;Inkson & Arthur, 2001;London, 1983;Rothwell & Arnold, 2007;Van Der Heijde & Van Der Heijden, 2006) but not in others such as protean and boundaryless career orientations, career adaptability, or career self-management (Briscoe & Hall, 2006;Hall, 2004;Kuijpers & Scheerens, 2006;Noe, 1996;Savickas, 2005;Stickland, 1996). The same is true of social and human capital, which are considered an integral part of career competencies and career capital (Eby et al 2003, Inkson & Arthur, 2001, and some definitions of employability (Fugate, et al, 2004;Rothwell & Arnold, 2007;Van Der Heijde & Van Der Heijden, 2006), but not protean and boundaryless career orientations, career motivation, or career adaptability (Briscoe & Hall, 2006;Hall, 2004;London, 1983;London & Noe, 1997;Savickas, 2005;Sullivan & Arthur, 2006). Second, the concepts overlap but also differ remarkably in terms of what they define as core constructs of SDCM and its antecedents or consequences.…”
Section: Similarities and Discrepancies Among Existing Conceptsmentioning
confidence: 99%
“…Second, the concepts overlap but also differ remarkably in terms of what they define as core constructs of SDCM and its antecedents or consequences. For example, personality characteristics are treated as integral parts of the concepts in some instances, for example, as part of career competencies and career capital (Eby, et al, 2003;Inkson & Arthur, 2001), employability (Fugate et al, 2004;Rothwell & Arnold, 2007;Van Der Heijde & Van Der Heijden, 2006), or career motivation (London, 1983). For others, personality dispositions are treated as antecedents, for example, for protean and boundaryless career orientations (Hall, 2004;Sullivan & Arthur, 2006), career adaptability (Morrison & Hall, 2002;Savickas, 1997), or career self-management (King, 2004;Kossek, et al, 1998;Raabe, et al, 2007).…”
Section: Similarities and Discrepancies Among Existing Conceptsmentioning
confidence: 99%
See 2 more Smart Citations